2018
DOI: 10.1111/jpc.14228
|View full text |Cite
|
Sign up to set email alerts
|

Online referral and immediate appointment selection system empowers families and improves access to public community paediatric clinics

Abstract: Aim We aimed to introduce a low‐cost combined online referral and immediate appointment selection system (CORIAS) to empower referrers and parents by allowing them to schedule an appointment at a time and location of their choosing in conjunction with the referrer at the time of referral. This was because an unacceptably high rate of reported lost referrals, combined with a high rate of failure to attend initial appointments (FTAs), was noted at a six‐site community paediatric clinic service. We aimed to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Open access scheduling, electronic consultation and referral systems, centralized scheduling systems, and the addition of advanced practitioners or PCPs to subspecialty departments have all been tested with mixed success on referral volume and patient wait times. [43][44][45][46][47][48][49][50][51] Several studies have shown that personalized appointment reminders, as opposed to automated [52][53][54] and longer term relationships with PCPs 25,36 are positively associated with appointment completion, suggesting the importance of personal connectivity and ongoing relationships. However, many of the most challenging barriers for families are problems such as transportation, work schedules, and child care, 35,55 which are difficult for health care organizations to address.…”
Section: Discussionmentioning
confidence: 99%
“…Open access scheduling, electronic consultation and referral systems, centralized scheduling systems, and the addition of advanced practitioners or PCPs to subspecialty departments have all been tested with mixed success on referral volume and patient wait times. [43][44][45][46][47][48][49][50][51] Several studies have shown that personalized appointment reminders, as opposed to automated [52][53][54] and longer term relationships with PCPs 25,36 are positively associated with appointment completion, suggesting the importance of personal connectivity and ongoing relationships. However, many of the most challenging barriers for families are problems such as transportation, work schedules, and child care, 35,55 which are difficult for health care organizations to address.…”
Section: Discussionmentioning
confidence: 99%
“…This could be caused by higher parental concern or higher acuity/need for cardiology referral. Implementing a process of online referrals with the ability to make an immediate appointment improves attendance of subspeciality clinic visits [45]. However, blanket implementation of certain interventions, particularly those that involve use of technological innovations, could worsen inequities present in subspecialty access to care [46].…”
Section: Discussionmentioning
confidence: 99%